Experimental Diagnostics and Characterization of Cold Atmospheric DBD Argon Plasma - Saha, Ram Lal Saha; Shah, Arun Kumar; Thakur, Bablu Kant; Shrestha, Rajendra; Nakarmi, Jeevan Jyoti (Patan Prospective Journal, 2025)
Cold atmospheric dielectric barrier discharge (DBD) plasmas have gained significant attention due to their versatility in material processing, biomedical treatment, and agricultural enhancement. In this study, an argon-based atmospheric DBD system was developed by two horizontal circular metallic electrodes of diameter 5.0 cm at 3.0 mm air gap with a glass dielectric of thickness 1.5 mm by applying AC voltage of 4.7 kV and frequency 20.0 kHz. The plasma was characterized through integrated electrical and optical diagnostics to evaluate its discharge behavior and plasma parameters. In the power balance method, Lissajous plot and V–I approaches were used to estimate electron density, while the current density method provided additional validation. Using Optical emission spectroscopy (OES), the electron temperature (Te) was determined as 0.88 and 1.03 eV employing the line intensity ratio and Boltzmann plot methods, whereas density (ne) was found as 3.2 x 1023 and 2.6 x 1016 m-3 by Saha–Boltzmann equation and Stark broadening method respectively. In the electrical method, ne was calculated as 1.3 x 1017, 1.8 x 1017, and 3.2 x 1018 m-3 using Lissajous plot, I–V, and current density methods respectively. The low electron temperature confirmed that the DBD plasma was a non-thermal. It is revealed that the Saha–Boltzmann method interprets more electrons than actually exist as it is based on LTE, while the Stark method measures the actual microfield effect of real electrons. The combined diagnostic approaches provide a reliable framework for deep understanding of cold atmospheric DBD plasmas for practical applications in low-temperature plasma processing.